Fiscal Decentralization and the Challenge of Hard Budget Constraints - Jonathan Rodden, , Gunnar S. Eskeland, and Jennie Litvack (The MIT Press, 2003)
This book is the product of a multicountry research project at the World Bank aimed at understanding the institutional settings in which decentralization may lead to large fiscal deficits and macroeconomic instability. The project was undertaken by the Decentralization Thematic Group, which found a significant gap in knowledge regarding the macroeconomic risks associated with decentralization. Not until there is a better understanding of how and why decentralization poses risks to macroeconomic stability can governments begin to design policies and institutions to safeguard against those risks. The study develops an analytical framework for considering the issues related to soft budget constraints for state and local governments, including the institutions, history, and policies that drive expectations for bailouts among subnational governments. Four mechanisms for disciplining subnational governments—fiscal, financial, political, and land markets—are developed and applied to each of the eleven country case studies (Argentina, Brazil, Canada, China, Germany, Hungary, India, Norway, South Africa, Ukraine, and the United States)